The Genetic Basis of Cellular Morphogenesis in the Filamentous Fungus Neurospora crassa - Seiler, Stephan (The American Society for Cell Biology, 2003)
Cellular polarity is a fundamental property of every cell. Due to their extremely fast growth rate (≥1 μm/s) and their highly elongated form, filamentous fungi represent a prime example of polarized growth and are an attractive model for the analysis of fundamental mechanisms underlying cellular polarity. To identify the critical components that contribute to polarized growth, we developed a large-scale genetic screen for the isolation of conditional mutants defective in this process in the model fungus Neurospora crassa. Phenotypic analysis and complementation tests of ca. 950 mutants identified more than 100 complementation groups that define 21 distinct morphological classes. The phenotypes include polarity defects over the whole hypha, more specific defects localized to hyphal tips or subapical regions, and defects in branch formation and growth directionality. To begin converting this mutant collection into meaningful biological information, we identified the defective genes in 45 mutants covering all phenotypic classes. These genes encode novel proteins as well as proteins which 1) regulate the actin or microtubule cytoskeleton, 2) are kinases or components of signal transduction pathways, 3) are part of the secretory pathway, or 4) have functions in cell wall formation or membrane biosynthesis. These findings highlight the dynamic nature of a fungal hypha and establish a molecular model for studies of hyphal growth and polarity.